Enhancing the Efficiency of a Quantum Heat Engine Beyond the Carnot Limit Through Coherence-Assisted Bath Coupling - Zain Nizam; Fatima Malik; Sara Hussain (Yayasan Adra Karima Hubbi, 2025)
The Carnot limit has long been considered the upper bound for the efficiency of heat engines, a fundamental concept in classical thermodynamics. However, in quantum systems, the possibility exists to surpass this classical boundary by exploiting quantum phenomena such as coherence. This study investigates the enhancement of a quantum heat engine's efficiency beyond the Carnot limit through coherence-assisted bath coupling. The primary objective of the research is to explore how quantum coherence between the system and its thermal bath can be used to reduce dissipation, optimize energy transfer, and increase efficiency. The research employs both theoretical modeling and computational simulations to analyze the performance of a quantum heat engine under varying coherence times and bath coupling strengths. By adjusting these parameters, the study examines the effects of coherence-assisted bath coupling on engine efficiency. The results demonstrate that, through careful manipulation of the coherence time and bath coupling strength, the quantum engine can exceed the Carnot efficiency, achieving a maximum efficiency of 78.7%. This finding indicates that quantum coherence can be used as a resource to enhance the performance of quantum heat engines. In conclusion, this study presents a new approach to quantum thermodynamics, showing that coherence-assisted bath coupling provides a viable path to enhancing quantum heat engine efficiency beyond classical limits.